A far away and nameless state: The travel narratives of Frieda Lawrence and Caitlin Thomas - Collins, KE (Edinburgh University Press, 2020)
Not I But the Wind ... and Leftover Life to Kill, the somewhat obscure mid-twentieth-century memoirs by Frieda Lawrence and Caitlin Thomas, were written, at least in part, in the countries that the authors eventually made their permanent home: New Mexico and Italy, respectively. While neither was marketed as a ‘travel book’, both works share many of the characteristics identified in the critical literature on women's travel writing, such as the way the memoirs were received as emotional outpourings with little authority outside the personal sphere and little of interest aside from their intimate knowledge of the authors' respective literary spouses. The analysis presented in this article shows that while Frieda and Caitlin sought to escape the gendered and classed strictures that so oppressed them in England, they applied them nevertheless to the individuals they encountered on their travels. Turning to the issue of viewpoints and watching, the article explores the frequency with which both narrators chose to position themselves behind windows as they set their scenes, indicating a more complex interrelation between watcher and watched than might first be assumed.